Multidrug-Resistant Bacteria on the Mobile Phones and Computer Keyboards of Healthcare University Students in Ghana - Michael Olu-Taiwo; Christian Afotey Laryea; David Kweku Mykels; Akua Obeng Forson (Canadian Journal of Infectious Diseases and Medical Microbiology)
Globally, mobile phones and computers (laptops and desktops) are indispensable part of human lives for communication, entertainment, and educational purposes. However, there are concerns about the increasing risk of bacterial contamination and antibiotic resistant trends from the surfaces of these devices. This study aims to assess bacterial contamination of mobile phones and computer keyboards and their resistant profile at the University of Ghana, Korle-Bu Campus, Accra. This was a cross-sectional study conducted from March to June 2017 with 240 swabs collected from the surfaces of mobile phones and computer keyboards used by healthcare students. Swabs were cultured on MacConkey, blood, and mannitol salt agar. Bacteria identification was performed with a standard bacteriological method. A total of 91 bacterial isolates were obtained from the devices, and they were tested against 9 commonly used antibiotics by the Kirby–Bauer disc method. The study revealed mobile phones and computer keyboards had contamination levels of 83.3% and 43.3%. Bacteria isolated included Staphylococcus epidermidis (25.4%), Klebsiella spp. (12.9%), Staphylococcus aureus (9.2%), Escherichia coli (6.7%), Pseudomonas spp. (5.4%), Enterobacter cloacae (2.1%), and Enterobacter spp. (1.7%). Overall, 91 bacterial isolates were highly resistant to ampicillin (96.7%) and tetracycline (75.8%) and moderately resistant to chloramphenicol (49.5%) with lower resistance to cefotaxime (18.7%), ceftadizime (14.2%), ciprofloxacin (25.3%), and gentamycin (24.7%). Additionally, 45.1% of isolates were multidrug resistant. Findings from this study revealed mobile phones and computer keyboards of healthcare students in the university were contaminated with pathogenic bacteria. Hence, frequent hand hygiene and disinfection of mobile phones and computer keyboard surfaces is encouraged to minimize the spread of resistant bacteria pathogens.